The Relationship between Training Climate and Self Efficacy to the Effectiveness of the Implementation of ISO 14001 Environmental Management System Training - Sidiq Purwoko; Ina Kusrini; M. Arif Musoddaq; Hardika Dwi Hermawan (Faculty of Engineering, Universitas Negeri Yogyakarta, 2018)
The environment is an inseparable element of human health. A good environmental management will bring benefit to human and surrounding. The successful implementation of International Standardized Management System (SML) ISO 14001 is determined by various factors and one of the factors is training. The purpose of this study was to analyze the correlation of training climate and self-efficacy to the effectiveness of ISO 14001 SML training. This study was categorized as a quantitative type with a cross-sectional design. The population consisted of participants with the total sampling of 90 respondents. The research variables include the training climate, self-efficacy and the effectiveness of the training. This study was conducted in PT XYZ, one of the manufacturing company in Jakarta. The results indicated that training climate and self-efficacy promote the effectiveness of the training with the percentages of 46.7% and 51.1% respectively. The prevalence of ratio that increases the opportunity for practical training is managers’ support (12.9), mastery experience (5.7), and opportunities to use learned abilities (0.2). In conclusion, the climate training and self-efficacy show a positive relationship with the effectiveness of training